PERLINDUNGAN HAK KONSUMEN MENGENAI PEMBERLAKUAN TARIF BATAS ATAS DAN BATAS BAWAH JASA ANGKUTAN UDARA BERDASARKAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN NOMOR 8 TAHUN 1999 (DALAM KASUS PENYEDIA LAYANAN LOW COST CARRIER (LCC) MASKAPAI LION AIR) - Nava Aprilda Wati; A.M. Tri Anggraini (Jurnal Hukum Adigama, 2019)
In early 2019 there was a very high increase in ticket prices. Ticket prices for domestic routes in Indonesia have not gone down, which is a complaint of consumers and make complaints to government agencies such as BPKN and YLKI. However, this has become the spotlight of the Minister of Transportation, raising the lower limit tariff, but this is actually considered ineffective because it can only protect airlines. This is considered to have violated consumer rights as stipulated in the UUPK. The issue of how the regulations and government policies in terms of tariff determination from the perspective of consumer protection and how the protection of consumer rights regarding the imposition of upper and lower limits of air transport services based on Law No. 8 of 1999. The author conducts research in this issue using normative methods supported by expert interview data. The author analyzes that this problem violates the consumer rights of Article 4 regulated by UUPK and analyzes from the Minister of Transportation Regulation PM 20 of 2019 concerning Procedures and Formulation of Calculation of Tariff Limit for Passengers in Economy Class Services for Scheduled Domestic Commercial Air Transport and Minister of Transportation Decree KM 106 of 2019 concerning the Tariff Limit on Passengers of Economy Class Scheduled Domestic Commercial Air Transport Services. The suggestion that can be given by the writer is that the ministry of transportation should oversee airlines in determining tariffs and services to remain balanced and not to the detriment of consumers.